Hypersensitivity to intravenous iron: classification, terminology, mechanisms and management. (25th October 2015) - Szebeni, J; Fishbane, S; Hedenus, M; Howaldt, S; Locatelli, F; Patni, S; Rampton, D; Weiss, G; Folkersen, J
Abstract : Intravenous (IV) iron therapy is widely used in iron deficiency anaemias when oral iron is not tolerated or ineffective. Administration of IV‐iron is considered a safe procedure, but severe hypersensitivity reactions (HSRs) can occur at a very low frequency. Recently, new guidelines have been published by the European Medicines Agency with the intention of making IV‐iron therapy safer; however, the current protocols are still non‐specific, non‐evidence‐based empirical measures which neglect the fact that the majority of IV‐iron reactions are not IgE‐mediated anaphylactic reactions. The field would benefit from new specific and effective methods for the prevention and treatment of these HSRs, and the main goal of this review was to highlight a possible new approach based on the assumption that IV‐iron reactions represent complement activation‐related pseudo‐allergy (CARPA), at least in part. The review compares the features of IV‐iron reactions to those of immune and non‐immune HSRs caused by a variety of other infused drugs and thus make indirect inferences on IV‐iron reactions. The process of comparison highlights many unresolved issues in allergy research, such as the unsettled terminology, multiple redundant classifications and a lack of validated animal models and lege artis clinical studies. Facts and arguments are listed in support of the involvement of CARPA in IV‐iron reactions, and the review addresses the mechanism of low reactogenic administration protocols (LRPs) based on slow infusion. It is suggested that consideration of CARPA and the use of LRPs might lead to useful new additions to the management of high‐risk IV‐iron patients.